Attenuated Clinical Forms of Tubulinopathies in Children and Adults: A Series of 24 Individuals - Durizot, Meghane; Burglen, Lydie; Garel, Catherine; Blondiaux, Eleonore; Riquet, Audrey; Floret, Valentine; Desportes, Vincent; Haanpää, Maria; Valenzuela, Maria Irene; Pinto, Anna Maria; Renieri, Alessandra; Vanneste, Michiel; et al. (ELSEVIER SCIENCE INC, 2025)
Background: Tubulinopathies are neurodevelopmental disorders caused by pathogenic variants in tubulin-encoding genes, typically presenting with intellectual disability (ID), epilepsy, motor impairments, and distinct brain malformations. While most cases are de novo and severe, recent reports suggest the existence of milder imaging and clinical phenotypes, including familial cases with attenuated symptoms.
Methods: Through international collaboration, clinical, imaging, and molecular data were collected from 24 individuals (≥ 4 years old) across 16 families with pathogenic or likely pathogenic variants in TUBA1A, TUBB2B, TUBB3, TUBB, or TUBB2A. Patients were selected based on absence of ID and availability of brain MRI. Genetic inheritance patterns and genotype-phenotype correlations were analyzed.
Results: Fifteen patients were identified through fetal or pediatric imaging and nine through familial investigations. No cases exhibited severe cortical gyration anomalies. TUBB3 was the most frequently mutated gene (12/24, 50%), and 7 out of 14 total variants were inherited. Two recurrent variants, TUBB3 p.(Pro357Leu) and TUBB p.(Asn52Ser), were associated with non-ID phenotypes in both the current cohort and literature.
Conclusions: This study broadens the spectrum of tubulinopathies to include mild imaging phenotypes with attenuated clinical features in children and adults. Absence of major cortical malformations, inherited mutations, and specific genetic variants may serve as favorable prognostic markers. These findings have important implications for genetic counseling, particularly in prenatal cases.